Calculation and analysis of predictable technological risk value of industrial objects in stationary operating conditions - Бойко, Тетяна Владиславівна; Вавулин, Пётр Андреевич (Eastern-European Journal of Enterprise Technologies, 2014)
The calculation algorithm of the predictable technological risk value of industrial objects during their operation is described in the paper. The algorithm is based on three methods: the Monte Carlo method, index method and method, based on the reliability theory elements. Using these methods in the present combination allows to avoid the problems, associated with the initial data uncertainty. It should be noted that the initial data uncertainty is a key problem to most common calculation methods. An example of calculating the technological risk for the system of seven water heaters in the HPP system was considered. The nominal failure probability value of individual elements of the system was calculated by the index method (calculation by the index method includes all the technological risk components, associated with the operating conditions of the object). This allows to avoid the initial data uncertainty problem during the calculation of technological risk of the entire system. The calculated probabilities are the initial data for the Monte Carlo method and the probabilistic method. After that, computer simulation of the system as a whole was performed by the Monte Carlo method. To obtain accurate results, it is recommended to carry out a sufficiently large number of iterations using the given method. For example, if the nominal element failure probability is 10-8, it is recommended to conduct at least 109 iterations. As a result, failure probabilities of each element of a complex technological system and the overall system were obtained. To verify the results, the fault tree construction method for the system under consideration was used. This test showed that the results are accurate, and each of the methods can be used to calculate the technological risk of industrial objects during operation.